MASS MEDIA TECHNOLOGY IN WILDLIFE TRADE IN INDONESIA - Urrasyidin, Andika (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study examines the role of technology, particularly social media, in facilitating illegal wildlife trade in Indonesia, as well as efforts to combat it. Online wildlife trade has grown along with technological advances, which provide criminals with wider access and anonymity that facilitate illegal transactions. Social media platforms and e-commerce have become the main channels for this trade, with perpetrators taking advantage of anonymity features and effective marketing through paid advertising and visual content. To address this problem, several mitigation efforts that can be made include increasing digital literacy for the community, collaborating with social media and e-commerce platforms to develop reporting mechanisms, developing artificial intelligence-based detection technology, and strengthening law enforcement. This study highlights the importance of collaboration between various parties, as well as the use of technology to detect and prevent wildlife trade more effectively.